2014
DOI: 10.1183/09031936.00005914
|View full text |Cite|
|
Sign up to set email alerts
|

Towards a close computed tomography monitoring approach for screen detected subsolid pulmonary nodules?

Abstract: Pulmonary subsolid nodules (SSNs) have a high likelihood of malignancy, but are often indolent. A conservative treatment approach may therefore be suitable. The aim of the current study was to evaluate whether close follow-up of SSNs with computed tomography may be a safe approach.The study population consisted of participants of the Dutch-Belgian lung cancer screening trial (Nederlands Leuvens Longkanker Screenings Onderzoek; NELSON). All SSNs detected during the trial were included in this analysis. Retrospe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
80
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(82 citation statements)
references
References 34 publications
2
80
0
Order By: Relevance
“…Furthermore, subsolid lung cancers were excluded, since the Syngo LungCARE© software package was not able to calculate the volume of sub-solid nodules (1.9% of all non-calcified nodules). Growth curves of nineteen subsolid NELSON lung cancers have been published elsewhere [33].…”
Section: Participantsmentioning
confidence: 99%
“…Furthermore, subsolid lung cancers were excluded, since the Syngo LungCARE© software package was not able to calculate the volume of sub-solid nodules (1.9% of all non-calcified nodules). Growth curves of nineteen subsolid NELSON lung cancers have been published elsewhere [33].…”
Section: Participantsmentioning
confidence: 99%
“…In the report by SCHOLTEN et al [8] in this issue of the ERJ shows that volume and mass doubling times of SSNs tend to be very long, and that a cut-off of <400 days would be unable to discriminate malignant from benign SSNs. The performance of volumetric software for subsolid nodules is less than ideal.…”
Section: @Erspublicationsmentioning
confidence: 99%
“…The performance of volumetric software for subsolid nodules is less than ideal. In fact, SCHOLTEN et al [8] resorted to manual determinations to obtain diameter, then volume and, hence, mass measurements, and moreover, one-third of their patients were ultimately referred for further workup based on a visual impression of growth. KIM et al [31] reported an error margin of -18% to +19% for automated mass measurements of SSNs, which is comparable with the results of SCHOLTEN et al [8].…”
Section: @Erspublicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reports from lung cancer screening trials showed that conservative management of pGGN provides optimal balance between risk and benefits. In asymptomatic subjects at high risk of lung cancer, pGGN did not progress to advanced stage lung cancer in several years after first documentation on CT (29)(30)(31)(32). Therefore, long-term active surveillance by low-dose CT (LDCT) is encouraged until the evidence of nodule progression.…”
mentioning
confidence: 99%